Towards extended seasonal forecasting of cholera-conducive coastal conditions in the Bengal delta - Ogata, Tomomichi; Racault, Marie-Fanny; Nonaka, Masami; Behera, Swadhin (Frontiers in Environmental Science, 2025)
Cholera is an infectious disease transmitted via contaminated water, affecting an estimated 1.3 to 4 million individuals annually and causing between 21,000 and 143,000 deaths worldwide. Forecasting cholera outbreak risk with sufficient lead time is critical for improving preparedness and supporting public health interventions. A key requirement is understanding the environmental conditions that favor Vibrio cholerae persistence outside human hosts. Recent studies have linked climate variability to coastal water conditions using the Satellite Water Marker (SWM) index. Building on this foundation, we present the first application of a dynamical seasonal prediction system (SINTEX-F2) to forecast SWM variability in the Bengal Delta during October-November up to 12 months in advance. Our approach combines SINTEX-F2-predicted climate indices–El Niño Southern Oscillation, Indian Ocean Dipole, and Indian summer monsoon rainfall–within a multilinear regression model framework. The extended SWM forecasts capture ∼50% of the observed variability over the past 2 decades (1997–2016). Notably, forecasts initialized in January exhibit enhanced skill despite longer lead times, linked to improved prediction of summer monsoon rainfall. Further analysis identifies subtropical North Pacific Sea surface temperature anomalies during June–July as a key precursor influencing monsoon forecast skill. These results demonstrate the feasibility of extending climate-informed cholera risk forecasts across multiple seasons, providing a novel foundation for the development of early warning systems for climate-sensitive infectious diseases.